1999
DOI: 10.1074/jbc.274.16.10877
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH and Multidrug Resistance Regulate Complement-mediated Cytotoxicity of Nucleated Human Cells

Abstract: showed that multidrug resistance (MDR) cells created by continuous selection with the vinca alkaloid vincristine (HL60 RV ؉ ) or by retroviral infection (K562/human MDR 1 cells) exhibited significant resistance to complement-mediated cytotoxicity (CMC). This resistance was due to the presence of overexpressed P-glycoprotein (P-GP). In this paper, we probe the molecular mechanism of this phenomenon. We test whether the significant elevated intracellular pH (pH i ) that accompanies P-GP overexpression is suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…In agreement with these studies were those of Bomstein and Fishelson (14), who demonstrated that P-gp ϩve tumor cell lines were more sensitive to complement-mediated lysis compared with matched P-gp Ϫve parental cells. However, in contrast to these findings were two reports demonstrating a role for functional P-gp in inhibiting membrane damage by complement (15,16). The authors of these studies presented evidence suggesting that P-gp-mediated intracellular alkalinization (pH i ) and/or decreased plasma membrane potential (V max ) resulted in a reduction in the rate of formation of the "membrane attack complex" (MAC) at the cell surface.…”
mentioning
confidence: 43%
See 1 more Smart Citation
“…In agreement with these studies were those of Bomstein and Fishelson (14), who demonstrated that P-gp ϩve tumor cell lines were more sensitive to complement-mediated lysis compared with matched P-gp Ϫve parental cells. However, in contrast to these findings were two reports demonstrating a role for functional P-gp in inhibiting membrane damage by complement (15,16). The authors of these studies presented evidence suggesting that P-gp-mediated intracellular alkalinization (pH i ) and/or decreased plasma membrane potential (V max ) resulted in a reduction in the rate of formation of the "membrane attack complex" (MAC) at the cell surface.…”
mentioning
confidence: 43%
“…Functional MACs consist of complement components C5b, C6, C7, C8, and multiple C9 molecules to form pores of ϳ100 Å (17). Expression of functional P-gp was shown to correlate with a reduction in the rate of MAC formation rather than the molecular stoichiometry of MAC complexes (16). It was hypothesized that altered pH i and/or V max may somehow directly or indirectly affect C9 polymerization, resulting in a net loss of functional MAC formation (16).…”
mentioning
confidence: 99%
“…[96][97][98][99] Recently, MDR1 has been demonstrated to regulate the apoptosis. [100][101][102][103][104][105][106][107][108] For example, Robinson et al reported that transfected MDR1 conferred resistance to apoptosis induced by serum starvation, which could be reversed by addition of verapamil. 104) However, little information is available concerning the role of MDR1 in the system.…”
Section: Mdr1 In Apoptosis and Immunologymentioning
confidence: 99%
“…107,108) Apoptosis is often preceded by intracellular acidification, 109,110) and MDR1 was suggested to delay the onset of the apoptosis via an increase of intracellular pH. 104) Some investigators pointed out that the change in intracellular pH contributed to the alteration of uptake by MDR1.…”
Section: Mdr1 In Apoptosis and Immunologymentioning
confidence: 99%
“…Further studies by several groups have suggested that MDR1 plays a role in apoptosis. For example, ectopic overexpression of MDR1 diminishes the apoptotic response induced by growth factor withdrawal (Robinson et al, 1997) decreases complement mediated cytotoxicity (Weisburg et al, 1999) and impairs the activation of caspase-dependent cell death pathways (Kojima et al, 1998;Smyth et al, 1998). In contrast, it is unknown if mdr1b overexpression a ects cell viability.…”
Section: Introductionmentioning
confidence: 99%